MICROSTRUCTURAL NATURE OF STRENGTHENING OF 12CR18NI10TI STEEL IRRADIATED UP TO 55DPA AFTER POST-IRRADIATION ANNEALINGS - Tsay, K.V. (Recent Contributions to Physics, 2018)
The microstructure changes in 12Cr18Ni10Ti austenitic steel – the material of a spent fuel assembly shroud of the BN-350 reactor – after a series of post-irradiation annealings in the range of 450-1050oC were studied using the transmission electron microscopy. The strengthening of irradiated steel was carried out in the model of dispersed barriers.